Métodos didácticos de waldorf para el fomento de la lectoescritura y su influencia en el pensamiento crítico en los estudiantes de séptimo año de educación básica de la unidad educativa “23 de Abril” parroquia Santa Fe, cantón Guaranda, provincia Bolívar, periodo 2022-2023” - Arevalo Agualongo, Rosa Olivia (2023)
This research has been carried out with the purpose of determining the literacy problems since this study facilitates overcoming the learning problems that occur with students in low school performance, allowing them to feel motivated and safe in the development of educational process. Education must develop the processes of reading and writing to train new generations, forming critical, purposeful and reflective students who can function and develop meaningful learning to be better in the social and cultural sphere. Reading and writing is the basis of quality teaching, teachers must deepen the techniques and methods to be able to guide in this extremely important process. Teachers are capable of training people who can understand when they read and understand what they write and thus achieve students with a good level of reading and spelling, thinking about the future of our students so that they achieve their goals and that they can function in a social environment. and every day be better. Critical thinking is one of our best allies to achieve development in students, so different methodologies must be applied so that the student learns in a different way